Effects of pH and Lactate on Hydrogen Sulfide Production by Oral Veillonella spp. - Washio, Jumpei (American Society for Microbiology, 2014)
Indigenous oral bacteria in the tongue coating such as Veillonella have been identified as the main producers of hydrogen sulfide (H(2)S), one of the major components of oral malodor. However, there is little information on the physiological properties of H(2)S production by oral Veillonella such as metabolic activity and oral environmental factors which may affect H(2)S production. Thus, in the present study, the H(2)S-producing activity of growing cells, resting cells, and cell extracts of oral Veillonella species and the effects of oral environmental factors, including pH and lactate, were investigated. Type strains of Veillonella atypica, Veillonella dispar, and Veillonella parvula were used. These Veillonella species produced H(2)S during growth in the presence of l-cysteine. Resting cells of these bacteria produced H(2)S from l-cysteine, and the cell extracts showed enzymatic activity to convert l-cysteine to H(2)S. H(2)S production by resting cells was higher at pH 6 to 7 and lower at pH 5. The presence of lactate markedly increased H(2)S production by resting cells (4.5- to 23.7-fold), while lactate had no effect on enzymatic activity in cell extracts. In addition to H(2)S, ammonia was produced in cell extracts of all the strains, indicating that H(2)S was produced by the catalysis of cystathionine γ-lyase (EC 4.4.1.1). Serine was also produced in cell extracts of V. atypica and V. parvula, suggesting the involvement of cystathionine β-synthase lyase (EC 4.2.1.22) in these strains. This study indicates that Veillonella produce H(2)S from l-cysteine and that their H(2)S production can be regulated by oral environmental factors, namely, pH and lactate.